2018
DOI: 10.1002/cjas.1483
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of XBRL Voluntary Disclosure for Stock Market Valuation: The Role of Corporate Governance

Abstract: The aim of this paper is to investigate the relevance for stock market pricing of accounting earnings of voluntary disclosures in XBRL files considering the quality of corporate governance. Results are the following. It appears that XBRL extensions attract financial analysts. Good governance is positively associated with voluntary XBRL extensions. We observe that XBRL extensions enhance the positive relationship between accounting earnings and stock price. However, this positive association is reduced for firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 67 publications
1
30
0
Order By: Relevance
“…A related stream of research examines how differences in the nature of digital reporting, in terms of the granularity of tagging and the use of firm-specific reporting 'extensions' , is associated with capital market indicators. More customised reporting, measured by XBRL extensions, is found to be positively associated with indicators of information efficiency (Li and Nwaeze 2015), value relevance (Cormier et al 2019) and negatively associated with the bid-ask spread (Li and Nwaeze 2015). Li and Nwaeze (2018) find that additional XBRL disclosure extensions used by preparers in excess of what is used in the industry are positively associated with analyst following and forecast accuracy and negatively associated with forecast dispersion.…”
Section: Capital Market Consequences Of Digital Corporate Reportingmentioning
confidence: 94%
“…A related stream of research examines how differences in the nature of digital reporting, in terms of the granularity of tagging and the use of firm-specific reporting 'extensions' , is associated with capital market indicators. More customised reporting, measured by XBRL extensions, is found to be positively associated with indicators of information efficiency (Li and Nwaeze 2015), value relevance (Cormier et al 2019) and negatively associated with the bid-ask spread (Li and Nwaeze 2015). Li and Nwaeze (2018) find that additional XBRL disclosure extensions used by preparers in excess of what is used in the industry are positively associated with analyst following and forecast accuracy and negatively associated with forecast dispersion.…”
Section: Capital Market Consequences Of Digital Corporate Reportingmentioning
confidence: 94%
“…However, the study of the relationship between XBRL adoption and earnings management is scarce. Even so, the results of the previous study regarding XBRL have revealed that there is a possibility of a strategic relationship between XBRL adoption and earnings quality (Cormier et al, 2018).…”
Section: 4hypothesis Developmentmentioning
confidence: 95%
“…XBRL can be used by anyone for free, without limitation, and publicly available. XBRL is also compatible with a wide range of hardware, operating system, and software exist (Cormier et al, 2018). The advantages of XBRL also make the exchange of business information between organizations going fast, accurate, effective, efficient, and digitalized well.…”
Section: Agency Theorymentioning
confidence: 99%
“…affiliated with the Illinois State University has the highest number of publication in the field of CSD based on Scopus index, with a total of 25 publications (to mention a few most popular; Patten, 2015;Sankara et al, 2019). Cornier, D. affiliated with École des sciences de la gestion is the runner up, contributing 14 articles to the field (Cormier et al, 2018;Gomez-Gutierrez & Cormier, 2018). Cho, C.H.…”
Section: Most Productive Authorsmentioning
confidence: 99%